2014
DOI: 10.1007/s10552-014-0511-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warfarin therapy on breast, colorectal, lung, and prostate cancer survival: a population-based cohort study using the Clinical Practice Research Datalink

Abstract: There was little evidence of associations between pre-diagnostic use of warfarin and cancer-specific mortality in lung, prostate, breast, or colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…The role of anti-coagulants such as warfarin and LMWH in prostate cancer remain controversial in the literature. Our study found a detrimental effect of warfarin however other retrospective reviews have found inconclusive or no effects of warfarin [ 29 31 ]. However, a recent single institution retrospective series of LMWH treated men (for deep venous thrombosis only) with docetaxel (17/247) suggested benefit on multi-variate analysis (HR, 0.48; P = .035) [ 19 ].…”
Section: Discussioncontrasting
confidence: 74%
“…The role of anti-coagulants such as warfarin and LMWH in prostate cancer remain controversial in the literature. Our study found a detrimental effect of warfarin however other retrospective reviews have found inconclusive or no effects of warfarin [ 29 31 ]. However, a recent single institution retrospective series of LMWH treated men (for deep venous thrombosis only) with docetaxel (17/247) suggested benefit on multi-variate analysis (HR, 0.48; P = .035) [ 19 ].…”
Section: Discussioncontrasting
confidence: 74%
“…In a cohort study including 12,186 men with PCa, but no information on stage no evidence was found for an association between PCa death and pre-diagnostic use of warfarin during a mean follow-up of 3.7 years [12]. In a sensitivity analysis post-diagnostic use was associated with an increased risk of PCa death.…”
Section: Discussionmentioning
confidence: 99%
“…Few observational studies examine the association between breast cancer mortality and anticoagulant use. To the authors' knowledge, only one previous study has been published on this topic, and it was limited to warfarin use [18]. That study found no risk association for pre-diagnostic warfarin use, but an increased risk of breast cancer death was associated with post-diagnostic warfarin use in subjects who had not previously received the drug (HR 1.36, 95% CI 1.12-1.64).…”
Section: Introductionmentioning
confidence: 91%